Prove that the result of differentiating arc tan (1-x^2) + arc cot (1-x^2) is 0.
- print Print
- list Cite
Expert Answers
calendarEducator since 2010
write12,551 answers
starTop subjects are Math, Science, and Business
We have to prove that the derivative of arc tan (1-x^2) + arc cot (1-x^2) is 0.
We know that the derivative of arc tan x = 1/[1 + (1-x^2)^2] and the derivative of arc cot x = -1 / [1 + (1-x^2)^2]
Let f(x) = arc tan (1-x^2) + arc cot (1-x^2)
f'(x) = -2x * 1/[1 + (1-x^2)^2] + (-2x)* -1/[1 + (1-x^2)^2]
=> -2x/[1 + (1-x^2)^2] + -(-2x)/[1 + (1-x^2)^2]
=> -2x/[1 + (1-x^2)^2] + 2x/[1 + (1-x^2)^2]
=> 0
The derivative of arc tan (1-x^2) + arc cot (1-x^2) = 0.
Related Questions
- Prove that limit of the function (a^x-1)/x=lna,x->0,using two methods.
- 1 Educator Answer
- Verify if limit of ln(1+x)/x is 1, x-->0
- 1 Educator Answer
- I need to evaluate the limit of function y=(1-cos2x)/x^2, using trigonometric identities. x...
- 1 Educator Answer
- Solve the derivative of expression: tan^2(ln(square root(4e^x+2x^2))) + cot^2(ln(square...
- 1 Educator Answer
- How can y=(x-1)^2+2(x-1)(x+2)+(x+2)^2 be differentiated in two different ways?
- 1 Educator Answer
We'll differentiate each term of the sum with respect to x:
d[arc tan (1-x^2)]/dx = (1-x^2)'/[1 + (1-x^2)^2]
d[arc tan (1-x^2)]/dx = -2x/[1 + (1-x^2)^2] (1)
d[arc cot (1-x^2)]/dx = -2x/-[1 + (1-x^2)^2]
d[arc cot (1-x^2)]/dx = 2x/[1 + (1-x^2)^2] (2)
We'll add (1) + (2):
d[arc tan (1-x^2) + arc cot (1-x^2)]/dx = (-2x+2x)/[1 + (1-x^2)^2]
Since the terms of numerator are eliminating each other, we'll get:
d[arc tan (1-x^2) + arc cot (1-x^2)]/dx = 0 q.e.d.
Student Answers